TIPOLOGI KAWASAN PERMUKIMAN KUMUH BERDASARKAN KARAKTERISTIK BANGUNAN HUNIAN DI KELURAHAN LEKOBALO KOTA GORONTALO - Yasin, Revina; Djau, Bambang; Jamaluddin, Fakhri; Sartika T. Zees, Dewi (Universitas Bina Taruna Gorontalo, 2024)
Slums are a problem faced by almost all major cities in Indonesia and other developing countries. The development of residential areas in the planning region is progressing rapidly, influenced by various policies that also affect spatial utilization activities. This study focuses on slums in Lekobalo Village, Gorontalo City, examining physical conditions, socio-economic conditions, and their impacts. Using a typological approach, an analysis was conducted on the characteristics of residential buildings, density, and irregularity. The aim is to identify the main problems and formulate intervention priorities for better infrastructure management and regional development. This was achieved through descriptive quantitative methods, utilizing both primary data (collected directly from the field) and secondary data (from relevant literature). The results indicate that the area is divided into two main categories: waterfront areas and hilly areas. Floods endanger communities living in the waterfront zones, while the hilly areas face significant challenges due to many houses being constructed on steep slopes without adhering to safe construction practices, thereby increasing the risk of landslides. Settlement patterns reveal a high concentration of population in limited areas, with a building irregularity rate of 59.63% and an average building density of 51.22%. Overall, the condition of residential buildings is generally poor, with 70.11% of buildings being classified as irregular.